2011
DOI: 10.1159/000327521
|View full text |Cite
|
Sign up to set email alerts
|

Can Bile Acids Be an Etiological Factor for Laryngeal Carcinoma?

Abstract: Purpose: The objective of this study is to show the accumulation of bile acids in laryngeal tissues of laryngeal carcinoma patients. Materials and Methods: The present study compared the total bile acid level in the hypopharyngeal tissue, tumor tissue, and blood of 21 primary laryngeal carcinoma patients (study group) to that in the hypopharyngeal tissue and blood of 15 patients with benign laryngeal lesions (control group). Results: The total bile acid level was significantly higher in the tumor and hypophary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…Tobacco and chronic alcohol have long been considered carcinogenic risk factors of laryngopharyngeal and hypopharyngeal cancer 2, 3. Gastroduodenal reflux disease (GDRD), a variant of gastro‐oesophageal reflux disease (GERD), has also recently been considered a risk factor that may exert independent carcinogenic potential related to chronic effects of toxic gastroduodenal fluid (GDF) on hypopharyngeal epithelial cells 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco and chronic alcohol have long been considered carcinogenic risk factors of laryngopharyngeal and hypopharyngeal cancer 2, 3. Gastroduodenal reflux disease (GDRD), a variant of gastro‐oesophageal reflux disease (GERD), has also recently been considered a risk factor that may exert independent carcinogenic potential related to chronic effects of toxic gastroduodenal fluid (GDF) on hypopharyngeal epithelial cells 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Although, it has been found that gastroduodenal refluxate can extend to the upper aerodigestive tract of patients,5, 6, 7 the tumorigenic effect of GDF is not yet well understood. Recent in vitro and in vivo studies have defined NF‐κB to be a possible mechanistic link between acidic bile or GDF and early pre‐neoplastic events in laryngopharyngeal mucosa 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Hypopharyngeal cancer is considered one of the most aggressive forms of head and neck malignancies with poor prognosis . There is evidence that bile‐containing duodenal contents are present in aspirates of patients with gastroesophageal reflux disease (GERD) and growing epidemiologic evidence supports their involvement in laryngopharyngeal neoplasia . Covington et al purport that the prevalence of bile in GERD may be greater than is believed by previous studies .…”
Section: Introductionmentioning
confidence: 99%
“…The American Cancer Society estimates in 2015 approximately 3,400 new hypopharyngeal cancer cases, with poor prognosis. Among known risk factors, such as tobacco smoking and alcohol use, gastroduodenal reflux (GDRD), a variant of gastro-esophageal reflux disease (GERD), is also considered a potential risk factor as there is growing evidence that GDRD may have carcinogenic potential related to chronic effects of toxic gastroduodenal fluids (GDFs) on hypopharyngeal mucosa (HM) [ 1 - 3 ]. However, the precise role of GDRD in hypopharyngeal carcinogenesis and its etiopathological mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%